PENEGAKAN HUKUM TINDAK PIDANA PENCEMARAN LINGKUNGAN HIDUP DENGAN MELAKUKAN OPENDUMPING LIMBAH (STUDI KASUS PUTUSAN NOMOR162/PID.SUS/2016/PT.SMG) - Rima Safira Perdani, - (2019)
This thesis discusses the environment where between humans and their environment there is a dynamic relationship. The author determines the formulation of the problem, namely the regulation regarding the crime of environmental pollution in relation to open dumping waste and the Decision of the Semarang High Court Number 162 / Pid.Sus / 2016 / PT. Smg concerning open dumping of waste in accordance with the applicable legal provisions. The author writes this thesis by using a normative juridical research method. Where arrangements that discuss open dumping of waste are contained in Article 60 of Law No. 32 of 2009 concerning Environmental Protection and Management which reads "everyone is prohibited from dumping waste and / or materials into environmental media without permission", so this applies to everyone, namely individuals and legal entities who dump waste into the media environment without permission. And the verdict which was decided in the case of environmental pollution by conducting an open dumping of waste with the defendant Cao Kefeng bin Cao Yio Li as the Factory Manager of PT. Starlight Garment, in Decision Number 162 / Pid.Sus / 2016 / Pt.Smg in accordance with the applicable provisions of legislation, namely Article 104 of Act Number 32 of 2009 concerning Protection and Management of the Environment, because it fulfills the elements of criminal acts: Everyone, dumping waste into environmental media, and without permission